Compound heterozygous mutations in TTC7A cause familial multiple intestinal atresias and severe combined immunodeficiency - Yang, W.; Lee, P.P.W.; Thong, Meow Keong; Ramanujam, T.M.; Shanmugam, A.; Koh, M.T.; Chan, K.W.; Ying, D.; Wang, Y.; Shen, J.J.; Yang, J.; Lau, Y.L. (Wiley, 2015)
Familial multiple intestinal atresias is an autosomal recessive disease with or without combined immunodeficiency. In the last year, several reports have described mutations in the gene TTC7A as causal to the disease in different populations. However, exact correlation between different genotypes and various phenotypes are not clear. In this study, we report identification of novel compound heterozygous mutations in TTC7A gene in a Malay girl with familial multiple intestinal atresias and severe combined immunodeficiency (MIA-SCID) by whole exome sequencing. We found two mutations in TTC7A: one that destroyed a putative splicing acceptor at the junction of intron 17/exon 18 and one that introduced a stop codon that would truncate the last two amino acids of the encoded protein. Reviewing the recent reports on TTC7A mutations reveals correlation between the position and nature of the mutations with patient survival and clinical manifestations. Examination of public databases also suggests carrier status for healthy individuals, making a case for population screening on this gene, especially in populations with suspected frequent founder mutations.